2014
DOI: 10.4172/2157-7110.1000300
|View full text |Cite
|
Sign up to set email alerts
|

Oil Palm Leaf: A New Functional Food Ingredient for Health and Disease Prevention

Abstract: The Oil palm (Elaeis guineensis) leaves has 8% higher total polyphenols content than green tea extract and contains epigallocatechin, catechin, epicatechin, epigallocatechin gallate, epicatechin gallate amongst their various flavonoids glucosides. The health benefits of OPLE on breast cancer, diabetes, hypertension, inflammation, oxidative stress, neurodegeneration, cognitive functions, dyslipidemia, cardiovascular, liver, kidney and neuroprotective properties and hypercholesterol are reviewed. The OPLE have g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 40 publications
0
13
0
3
Order By: Relevance
“…The adsorption process was conducted over 24 h at 25 • C. The experiment was carried out on OPL extract solutions of different pH (5, 7, and 9; adjusted with 1 M HCl or 1 M NaOH), in triplicate. At 0, 5,10,15,20,25,30,40,50,60,120,180,240,300,360,480, and 1440 min time points, 0.125-mL aliquots of the treated OPL extract were withdrawn for TFC determination. The adsorption kinetics equation for each resin was accordingly established for each.…”
Section: Adsorption Kinetics Of Opl Total Flavonoids On the Selected mentioning
confidence: 99%
See 2 more Smart Citations
“…The adsorption process was conducted over 24 h at 25 • C. The experiment was carried out on OPL extract solutions of different pH (5, 7, and 9; adjusted with 1 M HCl or 1 M NaOH), in triplicate. At 0, 5,10,15,20,25,30,40,50,60,120,180,240,300,360,480, and 1440 min time points, 0.125-mL aliquots of the treated OPL extract were withdrawn for TFC determination. The adsorption kinetics equation for each resin was accordingly established for each.…”
Section: Adsorption Kinetics Of Opl Total Flavonoids On the Selected mentioning
confidence: 99%
“…Multiple interactions between the flavonoids and cross-linked polymeric XAD7HP resin through van der Waals forces and hydrogen bonding described the sorption processes. Therefore, by utilizing this method, the flavonoid-enriched fraction from crude OPL extract could be used as a potential bioactive ingredient in nutraceutical and pharmaceutical applications at minimum cost with optimum efficiency.Molecules 2020, 25, 778 2 of 17 shown to be safe for use in disease treatments based on the absence of adverse effects in several studies on rodents [5,6].Previous chemical investigations revealed that OPL extract is rich in flavonoids, mainly flavonoid O-glycosides and flavonoid C-glycosides [7]. As a class of compounds, flavonoids are well known to have positive effects on human health with reports of being hepatoprotective, antioxidative, and antidiabetic, among others [8].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The extract is reported to be incorporated into daily diet for improving cardiovascular system. Later, Mohamed et al (2014) reported that oil palm leaf has 8% higher total phenols content than green tea extract and contains epigallocatechin, catechin, epicatechin and epigallocatechin gallate. She reviewed the health benefits of oil palm leaf extract on breast cancer, diabetes, hypertension, inflammation, oxidative stress, neurodegeneration, cognitive functions, dyslipidemia, cardiovascular, liver, kidney and neuroprotective properties.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, oil palm leaves (OPL) make up the largest portion amounting to 53% dry weight of the total biomass [7]. As far as applicability of OPL is concerned, it is limited as ruminant feed and food flavoring agents [8]. Therefore, utilizing the cellulosic materials in OPL can improve agriculture sustainability while reducing the quantity of this biomass [9].…”
Section: ■ Introductionmentioning
confidence: 99%